CORRELATION BETWEEN CONSUMPTION OF VITAMIN A ON POSTPARTUM MOTHER AND BREAST MILK ADEQUACY - Icha Berliana; Munayarokh Munayarokh; Siti Rofi'ah (Poltekkes Kemenkes Semarang, 2019)
Background: Supplementation of vitamin A for postpartum mothers is needed to increase the amount of vitamin A in breast milk. Babies who suck the breast milk that contains enough vitamin A will be more immune and rarely suffered from infectious diseases. Purpose: The study aimed to determine the association of vitamin A consumption in postpartum mothers with adequacy of breast milk. Methods: This study is an analytical survey with cross-sectional design approach, condected within the work area of Mungkid Community Health Center, Magelang Regency with total sampling. The sample were 40 respondents. The data was retrieved by using a checklist observation sheet. Result: Statistical analysis with Spearman Rank test, obtained p-value of 0.000 so that 0.05, which means there was a significant relationship between consumption of vitamin A in postpartum mothers with adequate breastfeeding. Concluslion: Consumption of vitamin A in postpartum mothers correlated with breast milk adequacy. Midwives are expected to provide health care and health education, regarding vitamin A for postpartum women, and give 2 capsules of vitamin A to the mother after delivery. Postpartum mothers are suggested to obtain and consume 2 capsules of vitamin A after giving birth, because the benefits are many, especially with the adequacy of breast milk.